Manajemen Sekolah Ramah Anak: Studi Kasus di MTsN 6 Jombang - Akbarurrahman (LP. Ma'arif Janggan Magetan, 2022)
The delivery of the learning process in child-friendly schools must be supported by good management and based on child-friendly principles in order to create safe school environment and classroom atmosphere, fulfill children's rights and the best needs for children. purpose of this study is to determine the form of policy and implementation of child-friendly school management at MTSN 6 Jombang. This research is a qualitative research with the type of case study. Based on the results of the study, it was found that: 1. The form of policies implemented in the process of implementing child-friendly school management at MTSN 6 Jombang was based on four pillars of child-friendly school principles, namely non-violence, discrimination, best interests for children's growth, and respect for children. 2. Implementation of child-friendly school management begins with the planning and analysis stages of situations and conditions, organizing and forming teams, implementing programs, learning, infrastructure and program evaluation.